EFEKTIFITAS PENERAPAN GOOD GOVERNANCE DALAM PELAKSANAAN PEMILU DI INDONESIA YANG DILAKSANAKAN OLEH KPU - Novianty, Eka; Putri, Nabila; Prabu, Sendhy Putra Pratama (The Officium Nobile Journal, 2024)
Good governance is a concept of equal relations between government and society through changes in paradigm and thinking concepts. General elections are an indicator of the stability and democracy of a nation. General elections are a means to bring about the sovereignty of the people in the government of the Republic of Indonesia, based on the Pencasila, as ordered in the Constitution of the Unitary State of Indonesia of 1945. Quality elections fulfill the elements of independence, impartiality, and consider all voters fairly and equally. The public also has the right to supervise the holding of general elections. This research aims to determine the effectiveness of implementing good governance in the implementation of elections in Indonesia which are held by the general election commission. The research method uses qualitative methods with data sourced from journals, the internet and other trusted sources. The general elections organized by the KPU have implemented the principles of good governance such as representation, accountability, and legitimacy, as well as the principle of honesty and justice, all intended to a clean, good, and authoritative government. However, the Indonesian presidential election system does not use good governance and does not support election fairness. The results of previous elections in Indonesia show that the values of good governance have not been properly implemented at all stages of the election, especially in terms of legal principles.